VD_FINDINFO Jug / 2023 / 203 vom 28. November 2022 - VD Tribunal cantonal (2022)
REJET DE LA DEMANDE, LOI FÉDÉRALE SUR LA PROTECTION DES ANIMAUX | 106 CP, 42 al. 1 CP, 42 al. 4 CP, 44 ch. 1 CP, 47 CP, 26 al. 2 LPA